Innovations in sport for development and peace research. Issue 1 (2nd January 2017) - Chawansky, Megan; Hayhurst, Lyndsay; McDonald, Mary; van Ingen, Cathy
Abstract: This collection emerged from the Innovations in Sport for Development and Peace (SDP) Research Symposium held in Atlanta, GA, in 2016. The contributors explore new terrain in seeking to further an innovative agenda on SDP within development discourses and practices. The authors provide insights from plural empirical and theoretical domains, including critical, feminist, post-colonial, and cultural studies perspectives. A central goal of this collection is to anticipate, inspire, and shape the next phase of research in, on, and about SDP. A further goal is to connect SDP and development scholarship.